POTENSI PENGEMBANGAN TERNAK SAPI POTONG DI KECAMATAN TOMPASO BARAT - Sengkey, Natasya M; Salendu, A H.S; Wantasen, E .; Waleleng, P O.V (Universitas Sam Ratulangi, 2017)
ABSTRACTTHE POTENTIAL DEVELOPMENT OF Â BEEF CATTLE INWESTSUB TOMPASO DISTRICT.The objectives of this study was to find out the 1) various supporting resources for the development of beef cattle in West Sub Tompaso district, 2) Annalizing by LQ (Location Quotient) to determine the chosen location for beefcattle industry development in West Tompaso District. To know of cattle breeding potential in West sub Tompaso district.The sources of the research data were from secondary data which was collected from the district office of West Tompaso board of Agricultural, Fisheries and Forestry Extension. Office analysis model used Location Quotation (LQ) analysis model of potential and capacity of the area for beef cattle industry development in West Tompaso District. Based on the results of the analysis show that LQ sub TompasoWest has LQ 2.08 which is the base area. According to the results of maximum potential development of animal unit (AU) based on land resources was about 2.269,03 AU, capacity of increasing cow population-based area was about 1.180,53 AU, real cattle population was about 1.088,5AU, maximum potential based family unit was about 6.012 AU, and capacity of cattle population growth was about 4.923,5 AU. These values show that West Tompaso District has potential in developing beef cattle industry.Keywords: Beef cattle, potential areaÂ